2014
DOI: 10.1038/nmeth.3000
|View full text |Cite
|
Sign up to set email alerts
|

All-optical electrophysiology in mammalian neurons using engineered microbial rhodopsins

Abstract: All-optical electrophysiology—spatially resolved simultaneous optical perturbation and measurement of membrane voltage—would open new vistas in neuroscience research. We evolved two archaerhodopsin-based voltage indicators, QuasAr1 and 2, which show improved brightness and voltage sensitivity, microsecond response times, and produce no photocurrent. We engineered a novel channelrhodopsin actuator, CheRiff, which shows improved light sensitivity and kinetics, and spectral orthogonality to the QuasArs. A co-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
955
3
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 716 publications
(985 citation statements)
references
References 66 publications
22
955
3
5
Order By: Relevance
“…S6A). While our manuscript was in review, an Arch variant containing five mutations (P60S, T80S, D95H, D106H, and F161V) was reported with quantum yield of 8 × 10 −3 (1.5-fold less than Arch-7) (27). None of these individual mutations were identified in our evolution.…”
Section: Comparison Of Arch Variants With Other Fluorescent Proteinsmentioning
confidence: 76%
“…S6A). While our manuscript was in review, an Arch variant containing five mutations (P60S, T80S, D95H, D106H, and F161V) was reported with quantum yield of 8 × 10 −3 (1.5-fold less than Arch-7) (27). None of these individual mutations were identified in our evolution.…”
Section: Comparison Of Arch Variants With Other Fluorescent Proteinsmentioning
confidence: 76%
“…The combination of engineering and biology has allowed the precise quantification of contractile force in hPSC‐CMs (Ribeiro et al , 2015a), although it has been demonstrated that substrate stiffness plays a major role in the quantification of absolute force values (Feinberg et al , 2012; Ribeiro et al , 2015b). More recently, integrated technologies capable of simultaneously quantifying multiple parameters are being implemented with the view to providing reliable, high‐throughput tools for early preclinical stages of drug development (Hochbaum et al , 2014; Kijlstra et al , 2015; Rast et al , 2015; Song et al , 2015; Dempsey et al , 2016; Klimas et al , 2016). …”
Section: Assays and Readoutsmentioning
confidence: 99%
“…Small-molecule voltage sensors in particular are plagued by trade-offs in speed and sensitivity. More recently, genetically encoded fluorescent voltage sensors also show promise in terms of both speed and sensitivity (17)(18)(19)(20), but current methods are similarly limited by low one-and two-photon brightness (21).…”
mentioning
confidence: 99%